2010
DOI: 10.1007/s11604-010-0451-z
|View full text |Cite
|
Sign up to set email alerts
|

Midterm results of radiofrequency ablation versus nephrectomy for T1a renal cell carcinoma

Abstract: RF ablation provides RCC-related and DFS comparable to that found after nephrectomy with little loss of renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 38 publications
1
66
0
1
Order By: Relevance
“…In the latest controlled trials, percutaneous RFA and nephrectomy show comparable survival rates. Takaki et al compared percutaneous RFA with partial and radical nephrectomy, and reported 5-year cancer-specific survival rates of 100 % [4]. Turna et al also reported not significantly different cancer-specific survival rates between percutaneous RFA and partial nephrectomy (83.9 % vs. 100.0 %, respectively) but more cardiovascular complications in patients with long-term follow-up after nephrectomy [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the latest controlled trials, percutaneous RFA and nephrectomy show comparable survival rates. Takaki et al compared percutaneous RFA with partial and radical nephrectomy, and reported 5-year cancer-specific survival rates of 100 % [4]. Turna et al also reported not significantly different cancer-specific survival rates between percutaneous RFA and partial nephrectomy (83.9 % vs. 100.0 %, respectively) but more cardiovascular complications in patients with long-term follow-up after nephrectomy [5].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that radio frequency ablation (RFA) was suitable as an optimal ordinary option for small renal nodules [10]. However in the current report, ordinary treatment options also included active surveillance, partial nephrectomy, and radical nephrectomy, but did not include ablation.…”
Section: Discussionmentioning
confidence: 92%
“…Olweny et al [28] identified no significant difference between RFA and open partial nephrectomy for the treatment of T1a RCC in terms of 5-year disease-free survival, metastasis-free survival and local recurrence. RFA causes less deterioration of renal function than partial nephrectomy with similar oncological outcomes [29,30,31,32]. Psutka et al [33] in a study of 185 patients with Stage I renal tumour reported a 5-year recurrence-free survival of 96.1%.…”
Section: Accuracy and Reproducibility Of Quantitative Cardiac Mrimentioning
confidence: 97%